Analisis Banjir Sub DAS Cilemer HM 0+00 – HM 53+00 - Restu Wigati; Faiz Syafaat Arifin; Martia Dwi Lestari (Jurnal Ilmiah Rekayasa Sipil, 2020)
Rivers as natural water sources provide benefits for human life, flora, and fauna. The river is also a natural drainage channel to prevent flooding if it is managed properly. Most of the rainwater that falls to the land surface, flows to lower places due to gravity and eventually overflows into lakes or the sea. Along with changing conditions in the river basin, changes in land use and population growth have made the river not function optimally as it should have, causing flood disasters. A flood is an event of river water overflowing beyond the riverbed or standing water that occurs in low and non-drainable areas (SNI 2415: 2016). The purpose of this study was to determine the areas affected by the flood of the Cilemer River in Pandeglang Regency at HM 00 + 00 to HM 53 + 00, which can then produce policy recommendations in flood prevention so that the objectives are maximally achieved. Research supporting data was obtained from the Banten Province Water Resources Management Center. The analysis was carried out with several tests and the MAF method (Mean Annual Flood), process data using HEC-RAS 5.0.3, and ArcGIS 10.2.2 software. The results showed that the Cilemer River area HM 35 + 00 to HM 53 + 00 experienced flooding because the existing reservoir could not accommodate the planned discharge of 210.617 m3/s in Pagelaran and Patia areas, Pandeglang Regency.